A New Chemometric Strategy in Electrochemical Method Optimization for the Quantification of Cefdinir in Tablets, Effervescent Tablets and Suspension Samples. Issue 3 (5th December 2019) - Dinç, Erdal; Dermiş, Saadet; Can Akcasoy, Seda; Ceren Ertekin, Zehra
Abstract: A new voltammetric method, based on the use of single‐use pencil graphite electrode, was developed for the quantitative determination of cefdinir by square wave voltammetry. Chemometric optimization strategy was used to select the suitable values for three experimental parameters (pH of the supporting electrolyte, frequency and square wave amplitude) by applying a 3 3 full factorial design model. The optimal voltammetric conditions were found to be pH 5.0 for supporting electrolyte (Britton‐Robinson buffer), 43 mV for square wave amplitude and 108 Hz for frequency. Square wave voltammograms of calibration, validation and unknown samples were recorded between 0.0–1400 mV under the optimized voltammetric conditions. Linear regression equation was computed in the linear working range of 0.5–20 μg/mL by using the relationship between the concentration and peak current at 600 mV. The optimized voltammetric method was validated by assessing the analysis results of validation samples. Then the proposed method was applied for the quantitative determination of cefdinir in three different pharmaceutical preparations, namely film‐coated tablets, effervescent tablets and powder for oral suspension. It was concluded that the proposed voltammetric method was suitable for the quantitative analysis of commercial pharmaceutical preparations containing cefdinir. Abstract :